GM-008 Building a realistic and challenging continuous professional development programme in oncology for hospital pharmacy technicians. (25th February 2017) - Lefebvre, M; Meunier-Danel, V; Untereiner, C
Abstract : Background: Continuous professional development (CPD) has been mandatory for hospital pharmacy technicians (HPT) since 2009 in France. Its implementation is complex and faces many challenges: limited budgets and resources, expectations of adult learners, complexity of the continuing education system, limited number of programmes, tight schedules and heterogeneity of the continuing education system. Purpose: Our work focused on building a CPD programme in oncology that is realistic and challenging for HPT. Material and methods: For this project we used the model of educational engineering recommended by the High Authority of Health called 'ADDIE' (5 stages: analysis, design, development, implementation (setting-up) and evaluation (assessing)). Results: Conducting a survey among HPT highlighted two priorities: pharmacology of anticancer agents and risk management, and problems with non-compliance. The selected pedagogy is 'blended learning', which combines e-learning (24 e-courses with e-tests of 15 min), workshops and simulations (5 of 45 min each). The study of basic neuroscience led us to choose varied, short and repeated educational contents. The development of the pedagogical tools in seeking to minimise cost was €100/year. The A proposed schedule was as follows: September 2016, training and platform test; October 2016, finalisation of the programme; January 2017, CPD label application filing and launch after completion. The test platform has been well received and no major issues were raised. This method creates a custom programme tailored to the needs and expectations for a low financial cost. This still requires monitoring, animation, minimal funding and obtaining the CPD label. Conclusion: The first results of a satisfaction survey on one of the test modules are encouraging, but continuation of this project requires maintenance of the training programme over time as well as coupling to its CPD certification with the allocation of minimum maintenance funding. One could imagine the creation of a national platform on this model, open to all health professionals to pool resources and promote training. No conflict of interest